Sliding modecontrolled PV-based bootstrap converter system with enhanced response and voltage stability - Jyothi, Kesa; Varma, Pinni Srinivasa; Kishore, Dondapati Ravi; Jain, Hari Shankar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In this paper, a straightforward method for locating the controller in a PV-based bootstrap converter system is presented. Recent developments in control strategies and power electronics have made it possible to create PV-based DC-to-AC converters for AC drives that are connected to 3-phase loads. High voltage gain is intended to be produced by the bootstrap converter (BSC). The BSC's purpose is to control load voltage. This study compares the time specification performance of the proportional resonant controller (PRC) and the sliding mode control (SMC) for photovoltaic systems with bootstrap three phase inverter (PV-BSTPI). For the delicate loads, steady voltage is typically more important. The BS-TPI system incorporates a closed loop control to fast achieve constant voltage. Choosing the best control approach is the aim. It is observed that the steady state error of SMC is 1.67 which is better when compared to PRC.